Tumid Lupus Erythematosus Following Hyaluronic Acid Filler Injection: A Case Report - Kiatsurayanon, Chanisa; Sudtikoonaseth, Poonnawis; Sesavej, Thanasri; Kosidcanasup, Purich; Niyonsaba, François; Wichaidit, Mingkwan (Archives of Clinical and Medical Case Reports, 2022)
Dermal filling has increasingly become one of the most popular nonsurgical aesthetic procedures performed worldwide. Among several types of dermal fillers available, hyaluronic acid filler plays an integral role as the material of choice for treating volume reduction associated with skin aging due to its many favorable properties. Claimed to be safe, effective and biocompatible, injection of hyaluronic acid filler sometimes brings about undesirable outcomes. Adverse events from hyaluronic acid filler range from acute and temporary events such as bruising and erythema to more serious and long-lasting sequalae, including granulomas and vascular occlusion. Here, we report a case of tumid lupus erythematosus associated with hyaluronic acid filler injection. To the best of our knowledge, this is the first report of tumid lupus erythematosus following injection of a dermal filler. Treatment with oral hydroxychloroquine and topical tacrolimus resulted in gradual improvement of the skin lesions with no sign of recurrence after 3 months of followup. In summary, we highlight the potential immunologic complications of hyaluronic acid filler injection and encourage the role of intradermal pretesting in susceptible individuals.